2021
DOI: 10.1007/s10856-021-06523-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of in vitro biocompatibility and antibacterial activity of two calcium silicate-based materials

Abstract: This study is aimed at comparing and evaluating the biocompatibility and antibacterial activities of mineral trioxide aggregate (MTA) and iRoot BP Plus as novel retro-filling materials. Discs of both materials were prepared and incubated for 72 h to obtain material extracts in medium. Flow cytometry and the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay were used to assess the rate of apoptosis and proliferation of human periodontal ligament stem cells (hPDLSCs) when exposed to eluates of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In this regard, we used HCEMs, which are human cementoblast-like cell lines [ 27 ], because the evaluation of the cytocompatibility of materials with cementoblast-like cells is beneficial for clinical applications. Biological tests with inadequate material conditions, such as those related to setting and sterilization, have been conducted in many studies although a freshly mixed material is applied to the root canal in clinical practice and elution from this material affects surrounding periapical tissue [ 42 , 43 ]. As a result, we assessed cytocompatibility and biocompatibility using freshly mixed materials, ensuring that our method is more representative of clinical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, we used HCEMs, which are human cementoblast-like cell lines [ 27 ], because the evaluation of the cytocompatibility of materials with cementoblast-like cells is beneficial for clinical applications. Biological tests with inadequate material conditions, such as those related to setting and sterilization, have been conducted in many studies although a freshly mixed material is applied to the root canal in clinical practice and elution from this material affects surrounding periapical tissue [ 42 , 43 ]. As a result, we assessed cytocompatibility and biocompatibility using freshly mixed materials, ensuring that our method is more representative of clinical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Although MTA-based materials have been widely used for root perforation repair since their first introduction [ 12 ], various investigations of hydraulic calcium silicate-based cements (HCSC) have shown that BioRoot RCS (Septodont, Saint-Maur-des-Fosses, France) could be effectively used as a filler and seal the apical root perforation as well [ 13 ]. BioRoot RCS possesses all the necessary antibacterial, biocompatible and bioactive properties, which promote the regeneration of periapical tissues and contribute to the recruitment of osteo-odontogenic stem cells within the apical environment [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…MTA, accepted as the gold standard as a root-end filling material with its anti-inflammatory and osteogenic potential, as well as many favorable properties, has been evaluated in many studies 32 34 . nMTA, which contains tricalcium silicate (alite), dicalcium silicate (belite), calcium sulfate (as anhydrite), and a low amount of calcite that facilitates the formation of calcium hydroxide, has taken its place among the new products as an advanced version of MTA 35 .…”
Section: Discussionmentioning
confidence: 99%